Sex and Equipment Impact on Lifting Velocity and the Maximum Repetitions in Bench Press. - Pérez-Castilla, Alejandro; Martínez-Rubio, Carlos; Baena-Raya, Andrés; Díez-Fernández, David M.; Hernández-Martínez, Alba; Rodríguez-Pérez, Manuel Antonio (International Journal of Sports Medicine, 2024)
This study investigated how equipment and sex affect the prediction accuracy of the maximum number of repetitions performed to failure (RTF) using the fastest mean velocity of the set (MVfastest). Sixteen men and twelve women completed four sessions (two using free-weight equipment and two sessions using the Smith machine). Each session involved three sets of repetitions to failure against the 65%, 75%, and 85% of the one-repetition maximum, interspersed by 10-min of rest. The goodness-of-fit of the individualized RTF-MVfastest relationships was comparable between both equipment types and sexes (P ≥0.510). Moreover, there were not significant differences in the MVfastest associated with RTF between equipment types (P ≥0.258). However, the MVfastest associated with RTF was higher for men than for women in repetitions 6 to 15 (P ≤0.043; ES≥0.69). In addition, the absolute errors when predicting RTF showed no significant differences between equipment types and loads (P <0.444). Specifically, these RTF estimates were within an acceptable range for men (<2 repetitions), but not for women (≥2 repetitions) (main effect of sex: P ≤0.018; ES≥0.58). These findings suggest that individualized RTF-MVfastest equations estimate the RTF with an acceptable precision in men during bench press exercises in both equipment types but exhibit lower precision for women.